(untitled) (Revista Inclusiones, 2021)
The Covid-19 pandemic is causing an unprecedented global crisis which impacts all spheres of individual and social life. Multidisciplinary and comparative research on the pandemic impact deserves more attention because of significant country variations in outbreaks, anti-epidemic policy response and population reactions. The necessity of highquality survey data in comparative and cross national perspective in times of a pandemic is addressed by Survey of Health, Ageing and Retirement in Europe (SHARE)1 . SHARE is the largest pan-European social panel study of health, social, economic and environmental policies over the life-course. From 2004 until today SHARE includes 380,000 in-depth interviews with 140,000 people aged 50 or older from 28 European countries and Israel. In the beginning of June 2020 Survey of Health, Ageing and Retirement in Europe started data collection of special “SHARE Corona Survey”, providing high-quality cross-national comparative data on the impact of Covid-19 pandemic. SHARE based research of the pandemic impact benefits also with its longitudinal design, and multidisciplinary content, combining social, economic and health variables. Special issue ‘Ageing in times of a pandemic’ of Revista Inclusiones is initiated by Ekaterina Markova and Gabriela Yordanova from the Institute of Philosophy and Sociology at the Bulgarian Academy of Sciences (IPS-BAS), coordinating the Bulgarian research infrastructure SHARE-ERIC Bulgaria2 and with the support of Bulgarian Ministry of Education and Science within National Roadmap for Research infrastructures3 . Guest editorial board of this special issue includes experienced researchers from Bulgaria and Croatia: Dr. Alexander Katrandzhiev (SWU “Neofit Rilski, Blagoevgrad), Prof. Gabriela Yordanova (Bulgarian Academy of Sciences), Dr. Ekaterina Markova (Bulgarian Academy of Sciences), Prof. Alexey Pamporov (Bulgarian Academy of Sciences), Prof. Ekaterina Tosheva (UNWE - Sofia), Prof. Šime Smolić (University of Zagreb), Prof. Ivan Čipin (University of Zagreb). The focus of special issue ‘Ageing in times of a pandemic’ is on recent developments in South-East European countries within the global pandemic. This research effort brings together scholars with an interest in multidisciplinary (social, economic and health) analyses in crisis development, based on SHARE data in cross-national and European perspective. Special interest is focused on impact of the Covid-19 pandemic on population aged 50 years and older and the volume includes 7 original SHARE based research articles, distributed in two thematic areas: